Phytochemical Analysis and Antimalarial Activity Aqueous Extract of Lecaniodiscus cupanioides Root - Mikhail Olugbemiro Nafiu; Taoheed Adedeji Abdulsalam; Musbau Adewumi Akanji (Journal of Tropical Medicine)
Root aqueous extract of Lecaniodiscus cupanioides was evaluated for antimalarial activity and analyzed for its phytochemical constituents. Twenty-four (24) albino mice were infected by intraperitoneal injection of standard inoculum of chloroquine sensitive Plasmodium berghei (NK 65). The animals were randomly divided into 6 groups of 3 mice each. Group 1 served as the control while groups II–IV were orally administered 50, 150, and 250 mg/kg body weights of extract. Groups 5 and 6 received 1.75 and 5 mg/kg of artesunate and chloroquine, respectively. The results of the phytochemical analysis showed the presence of alkaloids (2.37%), saponin (0.336), tannin (0.012 per cent), phenol (0.008 per cent), and anthraquinone (0.002 per cent). There was 100 per cent parasite inhibition in the chloroquine group and 70 per cent in the 50 mg/kg body weight on day 12, respectively. The mean survival time (MST), for the control group was 14 days, artesunate 16 days, and chloroquine 30 days, while the groups that received 50 and 250 mg/kg body weight recorded similar MST of 17 days and the 150 mg/kg body weight group recorded 19 days. The results obtained indicated that the aqueous extract of Lecaniodiscus cupanioides may provide an alternative antimalarial.